Mechanisms for public participation in relation ti international instruments on Climate Change - Espinoza Galdames, Ariel (Revista de Derecho Ambiental, 2018)
Currently, there are no formal mechanisms in place to ensure citizen’s participation in the negotiation, ratification, repeal or implementation of international agreements on climate change. This may come as a paradox if we consider that environ-mental democracy is identified as a necessary condition to achieve objectives such as mitigation and adaptation in order to face climate change. To deal with this problem, it is essential to change the vision about the role and need of citizen’s participation, by establishing formal mechanisms to ensure it, thus avoiding the abusive exercise of executive powers in relation to international environmental agreements, and moreover, the government's lack of action on these matters.